Effectiveness of Psychoeducation to Reduce Relapse Among Substance Users: An Interventional Study - Abdulqadir, Salar Omar; Mustafa, Ibrahim Hasan; Hamad , Abdulqader Hussein (Kurdistan Journal of Applied Research, 2026)
Relapse rates among substance users are generally higher in the early stages following substance use cessation. Nevertheless, correctional facilities are seeking effective strategies to reduce the risk of relapse among incarcerated substance users. This study developed and assessed a psychoeducational program to reduce the risk of relapse among substance users using a quasi-experimental design. We recruited 102 incarcerated substance users from a correctional facility and divided them into two equal groups. The pretest, program implementation, and posttest were conducted from July 1, 2024, to March 2, 2025, using the Stimulant Relapse Risk Scale-35. Paired t-tests and a linear regression analysis were used to evaluate program effectiveness and identify the predictive factors for reducing the risks of relapse, respectively. The sample was predominantly male (82.2%). Approximately 51.2% and 56.4% participants in the control and experimental groups, respectively, were using methamphetamines. Participants in the experimental group showed a significant improvement following program implementation (p < 0.001). Significant predictors of greater improvement following the program’s implementation were good financial status, being divorced, living with a spouse, living alone, and using opium. Conversely, significant predictors of lower improvement included having a bachelor’s degree, having parents with substance use disorders, smoking fewer than 10 cigarettes per day, starting to smoke at an older age, and using alcohol. Our findings underscore the necessity of psychoeducational programs in correctional facilities to help substance users participate in programs, thereby reducing their risk of relapse.